1984
DOI: 10.1177/00220345840630090401
|View full text |Cite
|
Sign up to set email alerts
|

Incisional Biopsy and Seeding in Hamster Cheek Pouch Carcinoma

Abstract: Surgical blades were contaminated by doing incisional biopsies on DMBA-induced cheek pouch carcinomas in hamsters. Contaminated blades were then used to: (1) make cytologic smears; (2) make incisions in the mucosal surface of the lower lip; (3) make incisions in the ventral surface of the tongue; (4) make incisions in the untreated left cheek pouch; and (5) make incisions in the pre-shaved back. One group of animals was killed three hr post-surgery. The second group was killed seven wk post-surgery. Tissues we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…[9][10][11] Given that the great majority of oral SCC biopsies are of the incisional biopsy type -84% in our study -the question of biopsy-induced carcinoma spread is certainly an important one to answer as it may affect the survival of the majority of oral SCC patients. However, excisional biopsies may complicate margin localization when further excisions are required, and may require disfiguring and complicated surgery, which proves unnecessary when the lesion turns out to have been benign.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…[9][10][11] Given that the great majority of oral SCC biopsies are of the incisional biopsy type -84% in our study -the question of biopsy-induced carcinoma spread is certainly an important one to answer as it may affect the survival of the majority of oral SCC patients. However, excisional biopsies may complicate margin localization when further excisions are required, and may require disfiguring and complicated surgery, which proves unnecessary when the lesion turns out to have been benign.…”
Section: Discussionmentioning
confidence: 95%
“…They have shown that contamination of the surgical instrument with cancer cells did occur during incision of malignant lesions 10 and that malignant cancer spread can occur following an incisional biopsy procedure. 9,10 Interestingly, other animal studies of extraoral SCCs failed to support this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of clinicians are concerned that this procedure may spread cancer cells beyond the borders of tumor into the surrounding normal tissue; thus, promoting local spread as well as increasing the potential for metastasis. It has been indicated that surgical trauma inflicted on malignant tumors may increase their metastatic potency [80,81]. The major physical barriers to the migration of tumor cells during this process are connective tissue and basement membrane.…”
Section: Revisiting Incisional Biopsymentioning
confidence: 99%
“…The surgical intervention may destroy these barriers and facilitate invasion of vascular system at the site of the injury. A number of animal studies have been done which revealed that an incision into the oral cancer significantly increased the risk of regional lymph node metastasis [81][82][83]. Recently, it has been reported that there is an increased frequency of neck metastasis from stage I and II SCCs after incisional biopsy [84,85].…”
Section: Revisiting Incisional Biopsymentioning
confidence: 99%